2014
DOI: 10.1096/fj.13-247791
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated guluronate oligosaccharide enhances the antibacterial activities of macrophages

Abstract: Alginate from marine seaweeds is receiving continuous attention owing to its wide physiological activities. Herein, we sought to elucidate possible effects of alginate-derived polyguluronate (PG) and unsaturated guluronate oligosaccharide (GOS) on antibacterial activities of macrophages. Our results showed that, in contrast to PG, GOS markedly increased the phagocytosis of IgG-opsonized Escherichia coli and Staphylococcus aureus and further inhibited the survival of intracellular bacteria in macrophages. In li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 27 publications
7
34
0
Order By: Relevance
“…2C). Considering that GOS cannot alter CD14 expression in macrophages, which has been demonstrated by our previous publication 20 , we speculate that GOS could activate TLR4 and MD2, and trigger the MyD88-dependent pathway, leading to the production of pro-inflammatory cytokines without a requirement for CD14.
Figure 2GOS increases TLR4 expression and stimulates Akt/mTOR activation in RAW264.7 cells. ( A ) RAW264.7 cells were treated with 1 mg/ml GOS for 24 h, and TLR4 expression was evaluated by immunofluorescence analysis using an anti-TLR4 antibody.
…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…2C). Considering that GOS cannot alter CD14 expression in macrophages, which has been demonstrated by our previous publication 20 , we speculate that GOS could activate TLR4 and MD2, and trigger the MyD88-dependent pathway, leading to the production of pro-inflammatory cytokines without a requirement for CD14.
Figure 2GOS increases TLR4 expression and stimulates Akt/mTOR activation in RAW264.7 cells. ( A ) RAW264.7 cells were treated with 1 mg/ml GOS for 24 h, and TLR4 expression was evaluated by immunofluorescence analysis using an anti-TLR4 antibody.
…”
Section: Resultsmentioning
confidence: 61%
“…GOS has been found to augment the release of cytokines, such as tumour necrosis factor-α (TNF-α) 16 , and to induce the production of nitric oxide (NO) by activating NF-κB and MAPK signalling pathways 19 in RAW264.7 cells. GOS also promotes macrophage bactericidal activity by increasing phagocytosis in vitro and in vivo 20 . Furthermore, proteomic analysis revealed that GOS improves macrophage homeostasis 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Cells were incubated with Dulbecco’s Modified Eagle Medium (DMEM) with 10% Fetal Bovine Serum (FBS) at 37 °C and 5% CO 2 in a humidified environment. For bacterial inoculation into macrophage cells we followed similar protocols whereby phagocytosis was observed14. Colonies of EGFP expressing E. coli were transferred from the LB agar plate to a 14 mL round bottom tube filled with 3 mL of LB broth and 50  μ g/mL ampicillin medium for 20 hours at 37 °C and 225 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…Other examples include expression of fluorescent proteins fused to the LC-3 protein during the late phagosome-lysosome-autophagosome merging processes2. It is also common to fluorescently label the target pathogen; Xu and colleagues studied phagocytic activity by expressing fluorescent proteins in bacteria which were subsequently introduced into mammalian cultures14. Similarly, Oh et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation